Stereoselective Total Syntheses of Insect Juvenile Hormones JH 0 and JH I - Manabe, Atsushi; Ohfune, Yasufumi; Shinada, Tetsuro (Synlett, 2012)
Total syntheses of juvenile hormones JH 0 and JH I have been achieved by a new iterative enol tosylate homologation strategy.
Keywords: juvenile hormone; acyclic terpenoid; enol tosylate; Negishi coupling reaction